ChemInform Abstract: Asymmetric Synthesis of Pyrroloindolones by N‐Heterocyclic Carbene Catalyzed [2 + 3] Annulation of α‐Chloroaldehydes with Nitrovinylindoles. Issue 21 (27th May 2014) - Ni, Qijian; Zhang, Huan; Grossmann, Andre; Loh, Charles C. J.; Merkens, Carina; Enders, Dieter
Abstract The reaction can be scaled up.